Long‐term changes in aberrant DNA methylation and gastritis after Helicobacter pylori eradication focused on metachronous gastric cancer. Issue 5 (8th August 2022) - Tanaka, Ikko; Ono, Shoko; Watanabe, Yoshiyuki; Yamamoto, Hiroyuki; Oikawa, Ritsuko; Matsumoto, Shogo; Kubo, Marina; Nishimura, Yusuke; Shimoda, Yoshihiko; Ono, Masayoshi; Yamamoto, Keiko; Sakamoto, Naoya
Abstract: Background: A persistently high methylation level in gastric mucosa after Helicobacter pylori ( H. pylori ) eradication is presumed to be a risk for metachronous gastric cancer (MGC); however, long‐term changes in aberrant DNA methylation and histological gastritis have been unclear. Our aim was to examine changes in DNA methylation and histological gastritis according to the occurrence of MGC. Methods: Subjects were classified into three groups: 25 patients in whom MGCs occurred after the initial endoscopic resection (ER) for early gastric cancer and H. pylori eradication (MGC group), 17 patients in whom MGC did not occur for more than 5 years after the initial ER and H. pylori eradication (non‐MGC group) and 29 patients without a history of gastric cancer who succeeded in eradication more than 5 years ago (HP group). Aberrance of DNA methylation in three genes (miR‐124a‐3, EMX1, NKX6‐1) and histological score of atrophy and intestinal metaplasia (IM) were evaluated using biopsy samples before and more than a mean of 5 years after H. pylori eradication. Also, the mean Z ‐score was calculated using Z ‐score values of the three genes. Results: The methylation level of miR‐124a‐3 in the HP group and non‐MGC group and that of EMX1 in the HP group significantly decreased in the long term after eradication. In the MGC group, H. pylori eradication did not improve aberrant methylation, and the mean Z ‐score significantly increased. There were significant positive correlations between methylation levels in miR‐124a‐3 and EMX1 and histological findings after eradication. Conclusions: A persistently high methylation level after H. pylori eradication reflected precancerous mucosal conditions and led to long‐term MGC.